Assessement of Subtle Neurobehavioral Changes Induced By Potassium Nitrate In Rats And Theire Response Treatment By Ascorbic Acid - M. B. Mahmood (College of Education for Pure Sciences, 2010)
ABSTRACT The neurobehavioral effects of continuous dosing (as food additive) with potassium nitrate were assessed in albino rats. The rats were divided into the five groups, the control group have been fed in a concentrated forage (Barley, wheat, soybean, corn, wheatbrane) where as the treatment groups were fed with the same concentrated forage with the addition of potassium nitrate in different percentages (second group added 0.1%, 3rd group added 0.1% with 0.2%ascorbic acid as antidote, 4th group added 0.2%, 5th group added 0.2%with0.4%ascorbic acid as antidote) respectively for 5 weeks. Potassium nitrate did not produce overt signs of toxicosis but significantly decreased the open-field activity and also decreased the number of rearing during the open-field activity test, they reached to minimum level at the 4th week of treatment were reported, these decrease were followed gradual elevation to reach that values of the control group level at the end of study period. Potassium nitrate significant delayed the negative geotaxis at 45° angle and retain to reach the control level in 5th week in .The treated rats also suffered from a gradual increase in the body weight in comparison with pretreatment values, where as there was no effective significant the number of fecal boluses and swimming endurance. In this study the ascorbic acid (as antidote) in group 5 (0.4% with 0.2% potassium nitrate) differed significantly with group 4 (0.2% potassium nitrate only) that means the ascorbic acid give good result when it used for treatment of nitrate poisoning in animals. The results support the notion that in the absence of overt signs of toxicosis, neurobehavioral tests could be used to detect adverse behavioral changes induced by potassium nitrate.